Struggling over recognition: Honneth, political resistance, and violence - Pilapil, Renante D. (Frontiers in Sociology, 2026)
This paper explores the extent to which recognition struggles can be considered as legitimate by looking into both their ends and means. It probes into the conditions why such political resistance is waged and whether or not violence is warranted as a necessary means to achieve legitimate political objectives. The paper argues that to make struggles for recognition legitimate, they should be motivated by a just cause such as experiences of oppression as is the case of misrecognition. To prevent accusations that such experiences of injustice are subjective, they have to pass the test of the publicity criterion. Meanwhile, although recognition struggles can become violent particularly in the context of political resistance, they need not be. Violence can be resorted to as a last resort but it has to be regulated by the principle of proportionality, meaning, the use of violence does not lead to more injustices. In the final analysis, violence has to be kept at the minimum because what defines a social protest or political resistance is not the use of violence but restraint and control.